Research on the Mechanical Behavior of External Composite Steel Bar Under Cyclic Tension-Compression Loading - Xiushu Qu; Jialong Yang; Hongmeng Liu; Kexin Sun (Buildings)
A self-centering prefabricated concrete frame structure has good seismic performance, and its seismic capacity is mainly provided by the recovery force of the unbonded prestressing tendons and the energy-dissipation deformation capacity of embedded steel reinforcement. Relocating embedded reinforcement to external positions enables replaceability of energy dissipation components. And the configuration of external energy dissipation components is the primary factor influencing their energy dissipation capacity. Based on the existing external “Plug & Play” configuration, the internal steel bar size and material properties such as those of steel bar and filling material were varied in this study, and then, cyclic tension-compression experimental studies and numerical simulations were conducted to investigate the energy dissipation performance index and key influencing factors of this type of external composite steel bar. The research results showed that the composite steel bars designed in the experiments exhibited superior overall energy dissipation performance. Specimens utilizing Q345B steel as the core material outperformed those with Grade 30 steel. Moreover, the slenderness ratio of the composite steel bars and the diameter ratio between the end region and weakened segment of the internal steel bars were identified as critical parameters governing energy dissipation performance, and recommendations for optimal parameter ranges were discussed. This study provides a theoretical foundation for implementing external composite steel bars in self-centering structural systems.